2021
DOI: 10.3389/fphar.2021.636154
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Targeting of BET Proteins Attenuates Hyperuricemic Nephropathy in Rats

Abstract: Hyperuricemia is an independent risk factor for renal damage and promotes the progression of chronic kidney disease. In this study, we investigated the effect of I-BET151, a small-molecule inhibitor targeting the bromodomain and extraterminal (BET) proteins, on the development of hyperuricemic nephropathy (HN), and the mechanisms involved. Expression levels of bromodomain-containing protein 2 and 4, but not 3 were increased in the kidney of rats with HN; administration of I-BET151 effectively prevented renal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…Moreover, I-BET151 was effective in inhibiting the activation of transcription factors and growth factor receptors, such as c-Myc, P53, EGFR, and PDGFR, and reduced cell cycle arrested at G2/M phase ( Xiong et al, 2016 ). Recently, we further examined the effect of I-BET151 on the development of hyperuricemic nephropathy (HN) in a rat model and found that expression of Brd2 and Brd4, but not that of Brd3 was elevated in the injured kidney ( Xiong et al, 2021 ). Treatment with I-BET151 significantly prevented renal dysfunction, decreased urine microalbumin, and attenuated renal fibrosis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, I-BET151 was effective in inhibiting the activation of transcription factors and growth factor receptors, such as c-Myc, P53, EGFR, and PDGFR, and reduced cell cycle arrested at G2/M phase ( Xiong et al, 2016 ). Recently, we further examined the effect of I-BET151 on the development of hyperuricemic nephropathy (HN) in a rat model and found that expression of Brd2 and Brd4, but not that of Brd3 was elevated in the injured kidney ( Xiong et al, 2021 ). Treatment with I-BET151 significantly prevented renal dysfunction, decreased urine microalbumin, and attenuated renal fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with I-BET151 significantly prevented renal dysfunction, decreased urine microalbumin, and attenuated renal fibrosis. Furthermore, I-BET151 reduced expression of TGF-β1, inhibited dephosphorylation of Smad3 and ERK1/2 and NF-kB, and suppressed inflammatory response in the kidney ( Xiong et al, 2021 ). Although we detected an increase in serum levels of uric acid and xanthine oxidase, an enzyme that catalyzes production of uric acid, and a decrease in the expression of renal organic anion transporter 1 and 3, which promote urate excretion in the model of HN, I-BET151 treatment did not affect these responses ( Xiong et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperuricemic nephropathy (HN) is a common clinical complication of hyperuricemia ( Dalbeth et al, 2021 ; Xiong et al, 2021 ). Excessive urinary acid deposition in the kidneys traditionally induces hyperuricemic nephropathy ( Johnson et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that the development and progression of HN can occur through multiple mechanisms that are independent of acid crystal formation, such as promoting autophagy and NLRP3-mediated inflammation, 9 , 10 inhibiting transforming growth factor (TGF)-β, extracellular signal-regulated kinase 1/2 (ERK1/2), and nuclear factor (NF)-κB signaling pathways. 11 Hyperuricemia can cause oxidative stress that induces the overproduction of mitochondrial reactive oxygen species (ROS) in renal tubular epithelial cells, which play an important role in the pathogenesis of HN tubulointerstitial fibrosis. 12 Oxidative stress that is generated by monosodium urate (MSU) crystals promotes renal cell apoptosis, which is induced through the mitochondrial caspase-dependent apoptosis pathway.…”
Section: Introductionmentioning
confidence: 99%